Electrophoretic deposition of plasma activated sub-micron alumina powder. Issue 8 (1st June 2018) - Drdlik, Daniel; Moravek, Tomas; Rahel, Jozef; Stupavska, Monika; Cihlar, Jaroslav; Drdlikova, Katarina; Maca, Karel
Abstract: The positive effect of plasma mediated treatment of powder fraction in water-based dispersion is a rather well documented fact. Despite its importance for ceramic processing, the applicability of plasma treatment of ceramic particles in a non-aqueous dispersions remains unexplored. In the presented article, a specific planar type of dielectric barrier discharge - Diffuse Coplanar Surface Barrier Discharge (DCSBD), operated in atmospheric pressure air was used for the surface activation of sub-micron alumina particles. These were consequently dispersed in organic solvent of 2-propanol and evaluated for the performance during the process of electrophoretic deposition (EPD). The surface of ceramic particles and the dispersion behaviour were investigated using thermogravimetric analysis, XPS, measurement of zeta potential and particle size distribution. Plasma treatment of ceramic particles had a substantial effect on the deposition rate, which caused a significant reduction of surface roughness and slight improvement of the density and mean grain size of the fabricated coatings. Moreover, the plasma treatment resulted in a simultaneous anodic and cathodic EPD.